2020
DOI: 10.1111/jonm.13233
|View full text |Cite
|
Sign up to set email alerts
|

Vigilance and sleepiness in nurses working 12‐hr shifts and their coping strategies

Abstract: Nursing staff are the largest group of professionals in the health care team that provides 24-hr patient care across a 7-day workweek. The provision of most nursing care inevitably involves irregular hours, and more recently, nurses tend to work longer shifts (Rhéaume & Mullen, 2018). A 12-hr shift, which is now common for staff nurses, actually requires nurses to be in the workplace for more than 13 hr, due to extra tasks such as paperwork (Rhéaume & Mullen, 2018;Trinkoff et al., 2006). However, one advantage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Importantly, a recent study reported that nurses’ alertness considerably decreases during overtime hours (Min et al, 2021). These risks can interfere with nurses’ ability to complete necessary nursing activities without delay (Min, Kim, et al, 2021) and lead to patient safety issues such as making errors in medication administration, procedures or transcription (Caruso et al, 2019; Pélissier et al, 2020; Surani et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, a recent study reported that nurses’ alertness considerably decreases during overtime hours (Min et al, 2021). These risks can interfere with nurses’ ability to complete necessary nursing activities without delay (Min, Kim, et al, 2021) and lead to patient safety issues such as making errors in medication administration, procedures or transcription (Caruso et al, 2019; Pélissier et al, 2020; Surani et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Shift nurses have reported diminished alertness and sleepiness, and work performance deteriorations such as longer reaction times, difficulty in concentrating, inadequate attention to detail, and increased lapse rates (Ganesan et al, 2019; Geiger‐Brown et al, 2012; Sagherian et al, 2017). These risks may impact nurses’ ability to deliver high‐quality care and compromise patient safety (Pélissier et al, 2020; Royal College of Nursing, 2015). These risks increase when the shift work is combined with extended working hours (Caruso et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…
Most nurses work in shifts to deliver 24-h patient care globally (Pélissier et al, 2020). In South Korea, 82.1% of nurses in hospitals work in an eight-hour rapid rotating-shift system (i.e., different shifts every two to three days), including night shifts, and 2.8% work 12-h rotating shifts (Hospital Nurses Association, 2020).
…”
mentioning
confidence: 99%
“…Nurses are involved in shift work to provide 24‐h health care services for patients (Pélissier et al, 2020). South Korean hospitals require most nurses to work 8‐h rapid rotating shift work, including night shifts (Hospital Nurses Association, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Nurse fatigue leads to work performance deficits such as impaired alertness, long reaction times, concentration difficulties, lack of attention to detail and increased risk of errors (Geiger‐Brown et al, 2012; Johnson et al, 2010; Sagherian et al, 2017). It may affect nurses' ability to provide quality care and ensure patient safety (Pélissier et al, 2020; Royal College of Nursing, 2015). Fatigue, sleepiness and decreased alertness are more likely to be present when employees work rotating shifts owing to failed adaptation to circadian rhythm (Dall'Ora et al, 2016).…”
Section: Introductionmentioning
confidence: 99%